2003
DOI: 10.1034/j.1600-0463.2003.1110209.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of granulocytic Ehrlichia and Borrelia burgdorferi sensu lato in Ixodes ricinus ticks collected from Southwestern Finland and from Vormsi Island in Estonia

Abstract: Altogether, 343 adult and 111 nymphal Ixodes ricinus ticks collected from parks in Turku and suburban and rural islands of the Turku archipelago, Finland, and 100 adult I. ricinus ticks collected from Vormsi Island, Estonia, were included in this study. Using the polymerase chain reaction the ticks were examined for 16S rDNA of the Ehrlichia phagocytophila genogroup and for Borrelia burgdorferi sensu lato recA and flagellin genes. None of the Finnish ticks was found to be infected with E. phagocytophila, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 35 publications
4
37
1
Order By: Relevance
“…In addition, migratory birds may facilitate the expansion of Anaplasma- infected ticks to new regions [25]. Ap has been detected in ticks from Finland and neighbouring countries [26,27]. The prevalence of Ap infection has not yet been studied in Finnish people but studies in Denmark showed a high incidence of human granulocytic ehrlichiosis in humans exposed to ticks [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, migratory birds may facilitate the expansion of Anaplasma- infected ticks to new regions [25]. Ap has been detected in ticks from Finland and neighbouring countries [26,27]. The prevalence of Ap infection has not yet been studied in Finnish people but studies in Denmark showed a high incidence of human granulocytic ehrlichiosis in humans exposed to ticks [28].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, the overall prevalence ranges from 1.0% to 4.5% [35,36]. The overall prevalence in Europe ranges from 0.25% in Scotland to 57.1% in Italy [37,38] with great variation in every country: from 0.4% to 15% in France [39,40], from 3% to 57% in Italy [38,41,42], from 0.25% to 2% in Scotland [37], 3% in Estonia [43], from 5.1% to 8.7% in Austria [44,45], from 0.5% to 2.2% in Switzerland [46-48], up to 40.5% in Denmark [49] and up to 14% in various Eastern European countries [50-54]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the present cat had been outdoors in the same region. Anaplasma phagocytophilum has previously been detected in ticks in all of the neighboring countries; Estonia [21], European Russia [16], Sweden [22], and Norway [23]. …”
Section: Discussionmentioning
confidence: 99%